2016
DOI: 10.1186/s40104-016-0076-x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm cryodamage occurs after rapid freezing phase: flow cytometry approach and antioxidant enzymes activity at different stages of cryopreservation

Abstract: BackgroundIn order to improve the efficiency of bovine sperm cryopreservation process, it is important to understand how spermatozoa respond to differences in temperature as well as the ability to recover its own metabolism. The combination between flow cytometry approach and antioxidant enzymes activity allows a more sensible evaluation of sperm cell during cryopreservation. The aim of this study was to evaluate sperm attributes and antioxidant enzymes activity during different stages of cryopreservation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 53 publications
(52 reference statements)
2
54
0
2
Order By: Relevance
“…In recent years, several luorescent probes have shown that the cryopreservation process compromises the sperm plasma membrane integrity (PMI), resulting in reduced fertilizing capacity of postthaw semen [3][4][5][23][24][25][26][27][28][29]. Post-thaw sperm PMI has been assessed with diferent luorescent membrane probes, such as the dual SYBR-14 and propidium iodide (PI) assay [25,28] or membrane-permeable substrate carboxyluorescein diacetate (CFDA), a nonspeciic esterase substrate [24].…”
Section: Membrane Integritymentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, several luorescent probes have shown that the cryopreservation process compromises the sperm plasma membrane integrity (PMI), resulting in reduced fertilizing capacity of postthaw semen [3][4][5][23][24][25][26][27][28][29]. Post-thaw sperm PMI has been assessed with diferent luorescent membrane probes, such as the dual SYBR-14 and propidium iodide (PI) assay [25,28] or membrane-permeable substrate carboxyluorescein diacetate (CFDA), a nonspeciic esterase substrate [24].…”
Section: Membrane Integritymentioning
confidence: 99%
“…The chlortetracycline (CTC) luorescence assay has been used to detect capacitation-like changes in frozen-thawed spermatozoa, which may compromise their fertilizing ability [6,10,[22][23][24]29]. Cryo-induced changes in the acrosome membrane integrity (AMI) have been monitored by speciic Giemsa-staining technique [25] or with luorescent dyes, such as luorescein isothiocyanate (FITC)-conjugated PNA (peanut agglutinin) or conjugated PSA (Pisum sativum agglutinin), known as plant lectins, which bind to glycoproteins in the outer acrosomal membrane [4,5,26,27]. Studies have shown that the utilization of a triple staining-SYBR-14, phycoerythrin-conjugated PNA (PE-PNA), and PI (SYBR-14/PE-PNA/ PI)-to simultaneously evaluate the PMI and AMI of frozen-thawed bull spermatozoa can be used efectively to assess post-thaw semen viability [26][27][28].…”
Section: Membrane Integritymentioning
confidence: 99%
See 3 more Smart Citations